Searching for Saving Effects of Fiscal Policy : Evidence from Muslim Countries - Muhammad Zilal Hamzah; Abd. Ghafar b. Ismail (Indonesian Management and Accounting Research, 2013)
The studies on the effects of fiscal policy on the macroeconomic variables are well documented. But, the focus is only concentrated on interest rates, consumption, investment and economic growth. Based on a panel data model, this paper investigates whether the fiscal policy has an effect on national saving in Muslim countries. We will show that the response of national savings to fiscal policy are not limited to large fiscal contractions, but also, high or rapidly growing public debt may appear to be a good predictor of those affects. We also find that, in Muslim countries, the size and significance of the interaction terms are again stronger during expansions than during contractions.JEL classification: E21; E62; H31Keywords: fiscal policy; national saving; Muslim countries